The role of ideomotor representations in the displacement of the overall centre of mass - Kieleviainen, L.M.; Miasnikov, E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the influence of ideomotor representations on the displacement of the overall centre of mass. Methods and structure of the study. The scientific work was carried out at the Centre for Adaptive Physical Culture at Petrozavodsk State University. The experimental group consisted of 14 students. Postural stability was assessed using the Stabilan-01-2 stabiliser, equipped with a biological feedback function. To determine the influence of visual afferentation, basic indicators of postural balance were recorded using a simple Romberg test (with eyes open and closed) – stability was assessed with and without visual control in a standard static position. Results and conclusions. It has been established that ideomotor load affects posture by increasing the amplitude of oscillations of the general centre of mass without shifting its systematic position, which is recorded by stabilography and confirms the manifestation of the ideomotor act during postural control. The inclusion of ideomotor exercises with visual biological feedback in the system of adaptive physical education classes appears to be an effective method for stabilising posture in individuals with musculoskeletal disorders, including cerebral palsy.